Socio-Economic Impact of Digital Credit Accessibility: A Quantitative Analysis of Shopee Paylater Adoption and Consumptive Behavior - Mirza Hedismarlina Yuneline; Elvita Fujiyama Ruchiyat (Husnayain Business Review, 2026)
Purpose – This study investigates the psychological and technical determinants of digital credit-driven consumption within localized Indonesia administrative districts, specifically focusing on the influence of perceived ease of use and perceived usefulness on the consumptive behaviour of the community in Sumedang Regency. The objective of the study is to analyse the extent to which the Shopee Paylater feature catalyses unplanned and irrational spending patterns among diverse demographic groups. Methodology/approach – Utilizing a quantitative methodology characterized by descriptive and verification analysis, the study surveyed 100 respondents in Sumedang Regency through purposive sampling, employing multiple liner regression and classical assumption testing via SPSS software. Findings – The research findings indicate that perceived ease of use and perceived usefulness both exert a positive and significant influence on consumptive behaviour, both partially and simultaneously with the Technology Acceptance Model (TAM) variables collectively accounting for 38 percent of the variance in consumer spending habit. Novelty/value – The originality of this research lies in its localized focus on semi-urban regency, providing granular insight into how digital payment innovations transform financial behaviour outside of major city, where traditional credit penetration remains low. Keywords: Perceived Ease of Use, Perceived of Usefulness, Consumptive Behavior, Shopee Paylater